The researcher as instrument - how our capacity for empathy supports qualitative analysis of transcripts. - Stige, Signe Hjelen; Oddli, Hanne Weie; Hjeltnes, Aslak; Watson, Jeanne; Stige, Brynjulf (Qualitative Research in Psychology)
In this article we draw on literature from philosophy, history, and psychology to argue that empathy supports qualitative analysis of transcripts in several ways. We discuss examples of these processes both with data that we have co-created with our participants and data where we have not interacted with participants during data collection. What we suggest is not a new approach to analysis. Rather, we argue that the deliberate use of empathy bears potential to strengthen analysis across various analytical approaches. We explore five examples of how to access and harness our capacity for empathy as a resource in qualitative analysis: 1) Make time and room for prolonged engagement with data; 2) Use details and context actively when developing your understanding; 3) Practice decentering by actively seeking the perspective of the participants; 4) Attend to your own visceral experiences and body sensations; and 5) Utilize your capacity for imagination and creativity.